TINJAUAN HISTOLOGIS PEMBULUH DARAH TIKUS PUTIH (Rattus norvegicus) DIABETES YANG DIBERI REBUSAN DAGING BUAH MAHKOTA DEWA (Phaleria macrocarpha (Scheff.) Boerl.) - Sulistyoningrum, Evy; Kautsari, Septina; Susatyo, Priyo (Jurusan Kedokteran FK Unsoed, 2010)
Prevalence of Diabetes Mellitus among adult in Indonesia reached 4,1% in 1995 and projected to 6,5% in 2025. Complication of diabetes mellitus which come earlier and widely distributed yis atherosclerosis.Atherosklerosis can lead to other serious complications such as gangrene, stroke, cardiomiopathy, andcoronary artery diseases. This research was aimed to know the effect of Mahkota dewa (Phaleriamacrocarpha (Scheff.) Boerl.) boiled water to regeneration of aortaâs atherosclerosis post diabetic inductionwith alloxan. The research was conduct in four weeks to 25male albino rats (Rattus norvegicus) 3 monthaged, 120-180 grama weighed. The subjects was divided into five groups:positive control, negative control,A, B and C. A, B and C groups was treated Mahkota dewa boiled water with 4,5%, 9%, and 13,5%concentration respectively. The drug was administered orally. III, IV, and V groups are injected by alloxan toinduce diabetes. Atherosclerosis frequency was counted from histological section stained with Haematoxylineosin.Statistical analysis using Chi square analysis showed that Mahkota Dewa boiled water significantlyreduced atherosclerosis frequency in aorta. It can be concluded that Mahkota dewa (P.macrocarpha(Scheff.) Boerl.) regenerates atherosclerosis injury in diabetic blood vessel.